Dinâmica de inoculante microbiano encapsulado em solos sob diferentes condições abióticas - Graciano, Vanessa Araujo (Universidade Federal de São Carlos, 2023)
Phosphate fertilizers are widely used in order to achieve high crop productivity, but their production processes are expensive and can cause environmental damage. An alternative for fertilization is the use of P-solubilizing microorganisms (PSMs). However, a challenge during the inoculation with microorganisms is the high complexity of the soil in relation to biotic and abiotic factors. To overcome this limitation, a strategy to improve the abundance of PSMs is the use of encapsulated microorganisms as an inoculant. This strategy can protect the microorganisms from adverse environmental effects, physical and chemical factors of the soil, and increase the shelf-life time. The present study evaluated the abundance of free and encapsulated Bacillus subtilis in the artificial and clay soil in four experiments: a preliminary experiment in artificial soil at 40 ºC during 21 days; inoculation in artificial soil under different salinity and temperature conditions during 21 days; and two tests in clay soil under different salinity conditions at 30 ºC during 7 days. A polymeric gelatinized starch matrix was used for microbial encapsulation. The preliminary test resulted in a higher abundance of the encapsulated microorganism compared with the free. The results in the treatment with the inoculation in artificial soil showed that the encapsulated B. subtilis had a higher abundance under low temperature (15 ºC) and all salinity conditions (0, 10 and 20 mM NaCl) during the 21 days in comparison to free microorganism, with value up 26 times higher in 20 mM in 14 days. At 30 ºC, the abundance of the microorganism was also higher in all salinity conditions, but at 45 ºC there was no significant difference between free and encapsulated microorganisms. In the clay soil the encapsulated B. subtilis also had a higher abundance in comparison with the free microorganism, but this abundance decreased with high salinity condition (100 mM and 200 mM), reflecting how salinity stress affect the microorganisms developing. The results obtained here confirmed the potential of the encapsulated B. subtilis as a good strategy for fertilization in providing protection of the microorganisms in adverse abiotic conditions.
Dynamics of encapsulated microbial inoculant in soil under different abiotic conditions
Keywords: Bacillus subtilis; Salinidade; Temperatura; Biofertilizante; Solo; Salinity; Temperature; Biofertilizer; Soil; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::FERTILIZANTES